Serum 25-hydroxyvitamin-D level and atopic dermatitis severity in children - Laily Munawwarah; Rita Evalina; Sri Sofyani (Indonesian Pediatric Society, 2017)
Background Vitamin D plays an important role in the immune system. It inhibits B-lymphocyte proliferation and modulates the humoral response to suppress IgE production. Studies on the relationship between serum 25-hydroxyvitamin-D level and the severity of atopic dermatitis in several countries have had varying results.Objective To assess for a possible correlation between serum 25-hydroxyvitamin-D level and atopic dermatitis severity in children.Methods A cross-sectional study was conducted in 26 children with atopic dermatitis from September to December 2015. We evaluated the severity of disease using the Scoring of Atopic Dermatitis (SCORAD) index and measured serum 25-hydroxyvitamin-D levels. Spearmanâ€™s test was used to analyze for a correlation between serum 25-hydroxyvitamin-D level and the atopic dermatitis Â score in children with atopic dermatitis.Results Mean SCORAD index was 32.0 (SD 14.99) , with a range of 10.9 to 71.4. Mean serum 25-hydroxyvitamin-D level was 41.1 (SD 24.81) ng/mL, with a range of 10-137 ng/mL. There was a moderate correlation between serum 25-hydroxyvitamin-D level and the SCORAD index (r=-0.591), with higher SCORAD index associated with lower serum 25-hydroxyvitamin-D level (P=0.01).Conclusion There is a moderate correlation between serum 25-hydroxyvitamin-D level and the SCORAD index in children with atopic dermatitis.